Digital principles and applications - Leach, Donald P (Tata McGraw-Hill, 2006)
Digital principles and applications / Leach, Donald P. -- New Delhi: Tata McGraw-Hill, 2006 621.395 L434e6 6th ed No. of Copies : 2